2005
DOI: 10.1115/1.2391319
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Solar Photocatalytic Inactivation of Waterborne E. coli Using Tris (2,2′-bipyridine)ruthenium(II), Rose Bengal, and TiO2

Abstract: Background. The development of alternative processes to eliminate pathogenic agents in water is a matter of growing interest. Current drinking water disinfection procedures, such as chlorination and ozonation, can generate disinfection by-products with carcinogenic and mutagenic potential and are not readily applicable in isolated rural communities of less-favored countries. Solar disinfection processes are of particular interest to water treatment in sunny regions of the Earth. Solar light may be used to acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 33 publications
0
13
0
Order By: Relevance
“…It is expected that the inactivation rate increases with increase in photosensitizer concentration. This behavior is actually observed by many [40,42,84,96,97]. Acher et al [40,42] have studied the photoactivity of MB and RB in water treatment.…”
Section: Concentration Of Photosensitizermentioning
confidence: 53%
See 4 more Smart Citations
“…It is expected that the inactivation rate increases with increase in photosensitizer concentration. This behavior is actually observed by many [40,42,84,96,97]. Acher et al [40,42] have studied the photoactivity of MB and RB in water treatment.…”
Section: Concentration Of Photosensitizermentioning
confidence: 53%
“…However, Jemli et al [81] have reported the better activity of RB (di anionic) than MB (mono cationic) against fecal coliforms referring the enhanced activity of the former to better photophysical properties (high quantum yield of singlet oxygen and better absorption). Nonetheless, more recent studies proving that cationic dyes are more effective in destroying Gram-negative bacteria are published [50,52,84]. Caminos et al [82] have studied the effect of an anionic and four cationic porphyrins with different pattern of meso-substitution by 4-(3-N, N, N-trimethylammoniumpropoxy) phenyl (A) and 4-(trifluoromethyl) phenyl (B) groups.…”
Section: Factors Effecting Phototreatment Of Watermentioning
confidence: 99%
See 3 more Smart Citations